Fuelling on the wing: sensory ecology of hawkmoth foraging - Stöckl, Anna Lisa (J Comp Physiol A Neuroethol Sens Neural Behav Physiol, 2019)
Hawkmoths (Lepidoptera, Sphingidae) comprise around 1500 species, most of which forage on nectar from flowers in their adult stage, usually while hovering in front of the flower. The majority of species have a nocturnal lifestyle and are important nocturnal pollinators, but some species have turned to a diurnal lifestyle. Hawkmoths use visual and olfactory cues including CO(2) and humidity to detect and recognise rewarding flowers; they find the nectary in the flowers by means of mechanoreceptors on the proboscis and vision, evaluate it with gustatory receptors on the proboscis, and control their hovering flight position using antennal mechanoreception and vision. Here, we review what is presently known about the sensory organs and sensory-guided behaviour that control feeding behaviour of this fascinating pollinator taxon. We also suggest that more experiments on hawkmoth behaviour in natural settings are needed to fully appreciate their sensory capabilities.